Deciphering the Complexity of the Immune Cell Landscape in Kidney Allograft Rejection - George Terinte-Balcan; George Terinte-Balcan; George Terinte-Balcan; Emilie Lebraud; Julien Zuber; Dany Anglicheau; Dany Anglicheau; Gener Ismail; Gener Ismail; Marion Rabant; Marion Rabant (Transplant International)
While the Banff classification dichotomizes kidney allograft rejection based on the localization of the cells in the different compartments of the cortical kidney tissue [schematically interstitium for T cell mediated rejection (TCMR) and glomerular and peritubular capillaries for antibody-mediated rejection (AMR)], there is a growing evidences that subtyping the immune cells can help refine prognosis prediction and treatment tailoring, based on a better understanding of the pathophysiology of kidney allograft rejection. In the last few years, multiplex IF techniques and automatic counting systems as well as transcriptomics studies (bulk, single-cell and spatial techniques) have provided invaluable clues to further decipher the complex puzzle of rejection. In this review, we aim to better describe the inflammatory infiltrates that occur during the course of kidney transplant rejection (active AMR, chronic active AMR and acute and chronic active TCMR). We also discuss minor components of the inflammatory response (mastocytes, eosinophils, neutrophils, follicular dendritic cells). We conclude by discussing whether the over simplistic dichotomy between AMR and TCMR, currently used in clinical routine, remains relevant given the great diversity of immune actors involved in rejections.